2017
DOI: 10.5897/ajb2017.16154
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of proteases from edible mushrooms cultivated on amazonic tubers

Abstract: Proteases are important commercial enzymes, and among their numerous sources are the Basidiomycetes. The use of proteases in many industrial areas promotes the search for enzymes with new properties. The aim of this study is to produce and characterize peptidases of a biocomposite from mycelial biomass grown in Amazonic tubers. Lentinus citrinus DPUA 1535 and Pleurotus ostreatoroseus DPUA 1720 were cultivated on Dioscorea trifida, Manihot esculenta and Dioscorea alata supplemented with rice bran or manioc flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the presence of EDTA, PMSF and Pepstatin the proteases maintained catalytic activity of 100%, 99.58% and 99.47%, respectively. Machado et al (2017), Martim et al (2017a) and Brito et al (2019) reported inhibition of proteolytic activity of P. ostreatoroseus Singer (1961), P. albidus and L. crinitus in 95%, 62% and 11%, respectively, in the presence of iodoacetic acid.…”
Section: Partial Characterization Of Proteasesmentioning
confidence: 97%
“…In the presence of EDTA, PMSF and Pepstatin the proteases maintained catalytic activity of 100%, 99.58% and 99.47%, respectively. Machado et al (2017), Martim et al (2017a) and Brito et al (2019) reported inhibition of proteolytic activity of P. ostreatoroseus Singer (1961), P. albidus and L. crinitus in 95%, 62% and 11%, respectively, in the presence of iodoacetic acid.…”
Section: Partial Characterization Of Proteasesmentioning
confidence: 97%